Promotion of Aceh MSMes Products in Malaysia: Looking for Export Opportunities - Ghassan Raid Mutha Athif; Sartiyah; Nurshahira Binti Bustami; Aris Mahmudi; Altamis Ahnaf; Nuraidar; A. Rahmad Adi; Irfan Fajri; Mhd Yavishan Novinda; Ferizal; Safrida Ulyati; Noor Azuddin Bin Yakob (Asian Journal of Community Services, 2023)
The Promotion of Aceh MSME Products in Malaysia initiative by the Faculty of Economics and Business, Syiah Kuala University, aims to explore export opportunities for products of Micro, Small, and Medium Enterprises (MSMEs) students fostered by lecturers. The community service method for increasing MSME product exports is carried out by providing training and promotion of student MSME actors and the products produced. That is following various other community service activities, namely conducting training on human resource management, especially actors and employees, and promoting MSMEs products. Post-training results on MSME products and student actors showed significant improvement in MSME management and product quality. The results of this service focused on the introduction and exhibition of MSME products at international events at Universiti Kebangsaan Malaysia.